Computer vision syndrome (CVS): the assessment of prevalence and associated risk factors among the students of the American University of Armenia. - Peter, Rishba Getzie; Giloyan, Aida; Harutyunyan, Tsovinar; Petrosyan, Varduhi (Journal of Public Health: From Theory to Practice (2198-1833), 2025)
Aim: Computer vision syndrome (CVS) is a major occupational threat in the twentyfirst century, leading to decreased sleep quality, reduced work efficiency, and depression. This study aimed to assess the prevalence of CVS and the associated risk factors among undergraduate students of the American University of Armenia (AUA). Subject and methods: An online survey was conducted among 143 students aged 18 years and above in June 2021. Participants provided information about their socio-demographics, health, smoking, duration of computer/video display terminal (VDT) device use, daily hours of computer use before and during the SARS-CoV-2 pandemic, and protective habits while using the computer/VDT devices. The Computer Vision Syndrome Questionnaire was used to assess the presence of CVS. Results: The mean age of participants was 19.7 (SD ± 1.37). The majority of participants were women (79.4%). Allergy was the most prevalent chronic disease in the sample (17.5%). Almost 62.2% of participants reported having refractive errors (REs). About 9.0% of the study sample were current smokers. Daily hours of computer use before and during SARS–CoV-2 pandemic were 5.5 and 10.0 respectively. Only 10.7% of participants were taking breaks every 20 minutes while using computer/VDT devices. The prevalence of CVS was 78.3%. The most commonly reported symptoms of CVS were eye redness (74.6%), headache (72.5%), itching eye (71.2%), burning eye (70.5%), tearing eye (66.7%), and blurred vision (63.4%). In the adjusted analysis, the presence of REs, sitting position, viewing distance in using the computer/VDT devices, and voluntary blinking were associated with CVS. Conclusion: This study found a high prevalence of CVS in the study population. Following the recommendations on correct sitting position and viewing distance while using computer/VDT devices might reduce the prevalence of CVS in the target population. The interventions should particularly focus on the students with REs who are disproportionately affected by CVS.